Programmable Zwitterionic Droplets as Biomolecular Sorters and Model of Membraneless Organelles (Adv. Mater. 4/2022). Issue 4 (27th January 2022) - Capasso Palmiero, Umberto; Paganini, Carolina; Kopp, Marie R. G.; Linsenmeier, Miriam; Küffner, Andreas M.; Arosio, Paolo
Abstract : Programmable Liquid Droplets In article number 2104837, Umberto Capasso Palmiero, Paolo Arosio, and co‐workers propose a strategy to produce programmable liquid droplets via liquid–liquid phase separation of associative zwitterionic polymers. With this approach, multiple properties of the droplets, such as composition and stimulus responsiveness, can be finely tuned, opening attractive applications in bioseparation and diagnostics.